Examination of the European Excellence Model for Quality Management in a number of faculties of the University of Basra - Dawood , A.L. Alaa; Saud, .Ahmed; A.P. Zaid Sadiq Majid, A.P. Zaid Sadiq Majid (The Gulf Economist, 2025)
The purpose of this research is to find out whether sustainable development can be achieved using an appropriate approach to developing quality systems, such as the European Foundation for Quality Management (EFQM) Excellence Model. It also aims to test the European Excellence Model in a number of university colleges with the aim of increasing their efficiency and effectiveness and improving the quality of their educational services through a strategy-linked quality systems development approach that includes a comprehensive analysis of risks, processes and stakeholders, as this model may be the most appropriate for the educational institution and consistent with the institution’s strategic objectives, culture, quality policy and key performance indicators. In addition to the above, the study also aims to identify and determine the level of colleges’ focus on sustainable development and benefit from the quality system based on the European Foundation for Quality Management (EFQM) Excellence Model. The approach followed in this study is the descriptive approach The results of the study indicate that the EFQM Excellence Model may provide a management framework and a comprehensive overview for colleges to identify needed improvements and promote the implementation of progress activities on the path of sustainable development, while providing a guiding method for focusing on sustainable development for colleges. Similar to these results, the study recommended that there is an urgent need to develop the vision and mission of the college and according to the developments taking place in the world in the field of quality, with the necessity of developing plans and mechanisms that are commensurate with the policy and strategy approved by the college for the purpose of implementing it easily, and increasing interest in performance results and developing programs to raise His grades to the level of ambition. Keywords: European model, EFQM, enablers, results, processes